Male behavior in colonies of the social wasp Polistes lanio (Hymenoptera, Vespidae) - Giannotti, Edilberto [UNESP] (My University, 2004)
Sixteen post-emergent colonies of Polistes lanio were studied while producing males in the course of the colonial cycle. Individually, they remained in the nest only 10.5 days (5-31, n=165). Twelve different male behaviors were observed: remaining immobile on the nest (82,8%), giving alarm (4,8%), flying out from the nest (2,4%), copulating on the nest (2,4%), being dominated (1,6%), self-grooming (1,2%), checking cells (1,2%), adult-adult trophallaxis (receiving food) (0,8%), larva-adult trophallaxis (0,8%), chewing prey and giving it to the larvae (0,8%), returning to the nest without food (0,8%), and fanning the nest (0,4%). In comparison to the behavioral repertory of females (28 items), they performed fewer tasks and remained immobile most of the time on the nest. Their behavior was largely related to self maintenance, but also included giving chewed prey to the larvae, giving alarm signals and fanning the nest.
Keywords: Hymenoptera; Lanio; Polistes; Polistes lanio; Vespidae